2018
DOI: 10.1194/jlr.m082180
|View full text |Cite
|
Sign up to set email alerts
|

ZAG alleviates HFD-induced insulin resistance accompanied with decreased lipid depot in skeletal muscle in mice

Abstract: diabetes, hypertension, etc. The causes of insulin resistance are complicated and may vary for different individuals. Nevertheless, the factor most commonly associated with insulin resistance is excess adiposity due to the increase in circulating fatty acids and ectopic lipids (1). Intramuscular lipids are an indispensable energy source for skeletal muscle. These lipids play pivotal roles in metabolism not only for skeletal muscle but also for the entire body. The accumulation of ectopic lipids in skeletal mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Kabil SL et al recently showed reduced hepatic ZAG expression in diabetic rats maintained on a high-fat diet (HFD) [21]. Additionally, one study showed that the overexpression of ZAG alleviated HFD-induced IR and decreased the lipid contents of muscles in mice [22]. Another study showed that ZAG overexpression could protect against nonalcoholic fatty liver disease (NAFLD) in vivo or in vitro by ameliorating hepatic steatosis, IR, and inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Kabil SL et al recently showed reduced hepatic ZAG expression in diabetic rats maintained on a high-fat diet (HFD) [21]. Additionally, one study showed that the overexpression of ZAG alleviated HFD-induced IR and decreased the lipid contents of muscles in mice [22]. Another study showed that ZAG overexpression could protect against nonalcoholic fatty liver disease (NAFLD) in vivo or in vitro by ameliorating hepatic steatosis, IR, and inflammation [23].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed beneficial effects of ZAG on glycaemic control. 29,34,38,[42][43][44]46,[49][50][51]54,56,59 ZAG promotes insulin sensitivity and glucose tolerance through the activation of insulin receptor substrate (IRS)/AKT signalling pathway. 34 Analysis of human adipose tissue samples showed a positive association between adipose tissue insulin sensitivity and the expression of GLUT4 mRNA and ZAG protein content in subcutaneous adipose tissue (P < .05).…”
Section: Glycaemic Indicesmentioning
confidence: 99%
“…52 In addition, a significant upregulation of lipolytic enzymes including phosphorylation of HSL and ATGL in the skeletal muscle of mice was observed after administration of ZAG (25 µg for 30 minutes). 54 Due to an increased use of lipids by muscle and brown adipose tissue after ZAG administration (50 µg/day intravenously, for 10 days) to mice, levels of triglyceride and non-esterified fatty acids decreased by 25% and 62%, respectively. 56 Moreover, injection of ZAG recombinant plasmid to mice fed a HFD led to a great reduction in hepatic triglyceride by increasing phosphorylated protein kinase A (PPKA) expression, promoting phosphorylation of HSL, and decreasing protein levels of stearoyl-CoAdesaturase1 (SCD1), acyl-CoA synthetase-1 (ACSS1), hepatic fatty acid translocase (CD36)…”
Section: Glycaemic Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a new adipocytokine, more and more attention is being paid to ZAG, aiming at the prevention of obesity and energy metabolism disorders [12,13]. In a previous study, we found that ZAG decreases skeletal muscle lipid content and, therefore, alleviates insulin resistance in high-fat mice [14]. However, whether ZAG exerts its function in the skeletal muscle energy metabolism during cold stress, and whether it is involved in the acclimation to low temperatures is still unknown.…”
mentioning
confidence: 99%